A quality-improvement optimization pilot of BariFit, a mobile health intervention to promote physical activity after bariatric surgery. Issue 2 (18th May 2020) - Klasnja, Predrag; Rosenberg, Dori E; Zhou, Jing; Anau, Jane; Gupta, Anirban; Arterburn, David E
Abstract: Bariatric surgery is the most effective treatment for severe obesity (body mass index >40), helping individuals lose, on average, 25%–29% of their body weight over the first year. However, many patients begin to plateau and regain weight within 12–24 months, and 20% of patients begin to regain weight within 6 months postsurgery. As physical activity (PA) is an important predictor of weight loss and maintenance postsurgery, there is a need for scalable, effective lifestyle interventions to help bariatric patients increase PA in order to maximize their weight loss and maintenance. To assess feasibility of using mobile health (mHealth) tools to support PA postsurgery, we conducted a quality-improvement optimization pilot of BariFit, an mHealth intervention that combines commercial devices and custom text messages. Fifty-one bariatric patients enrolled in a 16-week optimization pilot of BariFit. To assess feasibility, pre–post changes in PA were assessed using activPAL. In addition, the pilot randomized, using a 2 × 2 factorial design, two adaptive approaches to daily step goals (variable and 60th percentile goals) and provision of rest days (yes/no), and microrandomized provision of SMS-delivered activity suggestions five times a day for each participant. Adherence to using study equipment was over 95% at 16 weeks. Participants increased PA by 1, 866 steps from baseline to end-of-study ( p < .007). Participants who received variable step goals averaged 1, 141 more steps per day ( p = .096) than those who received 60th percentile goals. Activity suggestions had no effect. mHealth interventions are feasible for supporting PA postbariatric surgery.